Cultural Aesthetics of Human Body: A Contemporary Interpretation through Traditional Chinese Ink Artistry - Liu, Fulong; Saat, Mohammad Khizal Mohamed; Li, Sheng (Journal of Ecohumanism, 2025)
In contemporary artistic discourse, Dissociative Identity Disorder has emerged as a significant focus of cultural exploration. While the human body serves as a cultural vessel for expressing mental states through artistic mediums, traditional Chinese ink painting—despite its rich cultural heritage—has historically limited visual representation of the human form, creating a gap in artistic dialogue about mental health. This artistic research employs studio practice methodology to bridge traditional Chinese artistic elements with contemporary visual expression of the human body, specifically examining Dissociative Identity Disorder through a cultural lens. The findings demonstrate that through cultural innovation while preserving the essence of Chinese ink painting traditions, the human form can be effectively rendered to portray the psychological manifestations of Dissociative Identity Disorder. This artistic exploration not only expands the cultural vocabulary of Chinese ink painting but also creates a new artistic paradigm for its evolution in contemporary cultural discourse.